(untitled) - Keenan, Sean C. (Hoboken, 2015)
Financial Institution Advantage and the Optimization of Information Processing offers a key resource for understanding and implementing effective data governance practices and data modeling within financial organizations. Sean Keenan—a noted expert on the topic—outlines the strategic core competencies, includes best practices, and suggests a set of mechanisms for self-evaluation. He shows what it takes for an institution to evaluate its information processing capability and how to take the practical steps toward improving it.
Keywords: Công nghiệp dịch vụ tài chính,Tổ chức tài chính,Financial services industry,Financial institutions; Xử lý dữ liệu,Quản lý,Data processing,Management